Stable Water Use Efficiency under Climate Change of Three Sympatric Conifer Species at the Alpine Treeline - Wieser, Gerhard; Oberhuber, Walter; Gruber, Andreas; Leo, Marco; Matyssek, Rainer; Grams, Thorsten Erhard Edgar (Frontiers in Plant Science, 2016)
The ability of treeline associated conifers in the Central Alps to cope with recent climate warming and increasing CO2 concentration is still poorly understood. We determined tree ring stable carbon and oxygen isotope ratios of Pinus cembra, Picea abies and Larix decidua trees from 1975-2010. Stable isotope ratios were compared with leaf level gas exchange measurements carried out in situ between 1979 and 2007. Results indicate that tree ring derived intrinsic water-use efficiency (iWUE) of P. cembra, P. abies and L. decidua remained constant during the last 36 years despite climate warming and rising atmospheric CO2. Temporal patterns in Δ13C and Δ18O mirrored leaf level gas exchange assessments, suggesting parallel increases of CO2-fixation and stomatal conductance of treeline conifer species. As at the study site soil water availability was not a limiting factor iWUE remained largely stable throughout the study period. The stability in iWUE was accompanied by an increase in basal area increment (BAI) suggesting that treeline trees benefit from both recent climate warming and CO2 fertilization. Finally, our results suggest that iWUE may not change species composition at treeline in the Austrian Alps due to similar ecophysiological responses to climatic changes of the three sympatric study species.